Growth and Population Parameters of Panulirus penicillatus and Panulirus homarus in Labangka Tidal Waters, Indonesia - Evron Asrial; Erwin Rosadi; Hamid Hamid; Muhammad Ichsan; Ruly Isfatul Khasanah; Naning Dwi Sulystyaningsih; Agustin Dwi Sumiwi; Najiah Khalisah (Faculty of Fisheries and Marine Universitas Airlangga, 2020)
HighlightUtilization, Growth, and Population of Bullet Tuna (Auxis rochei Risso 1810) in Indian Ocean Southern Sumbawa (2020)Eligibility Status Kawakawa (Euthynnus affinis Cantor, 1849) from Lombok Strait and Indian Ocean Southern Sumbawa (2020)Biological Aspect of Parent Candidate of White-spotted Rabbitfish (Siganus canaliculatus) from Serewe Bay, Lombok Timur District (2020)Study of Sustainability in Management of Malabar Blood Snapper Fisheries in the Indian Ocean Coastal Waters, Sumbawa Regency (2020)Growth Rate and Survivorship of Acropora sp. Fragments that Transplanted on the Artificial Substrate Made from Fly Ash and Bottom Ash (2020)Reproductive Biological Aspect of Panulirus penicillatus in Sumbawa Island Waters, Indonesia (2019)Fisheries Resource Status of Spiny Lobster Panulirus penicillatus in Labangka Waters, South Sumbawa, Indonesia (2019)Growth Rate of Acropora formosa Coral Fragments Transplanted on Different Composition of Faba Kerbstone Artificial Reef (2019)Agribusiness of Edible Jellyfish Crambione mastigophora in Saleh Bay, NTB: Implementation of Sustainable Fisheries (2019)AbstractThe Labangka tidal waters, located south of Sumbawa Regency are the habitat and potential fishing ground for lobsters. The dominant species caught by the Labangka fishermen are the Panulirus penicillatus and P. homarus. Fishing pressure is one of the greatest factor influencing the biological and stock condition of lobsters in Labangka. The aim of this study is to determine the key attributes in growth and population parameters. Some attributes whose values are relatively stable compared to that of 2015, consist of conditional factors such as (old age), growth pattern (hypoallometric), growth coefficient (slow growth), exploitation rate (overexploited), and fishing rate (excessive fishing). While, attributes that have improved are carapace length at first capture (CLc) longer than 50% carapace length of infinity (0.5CLâˆž) and CL rate (CLc/0.5CLâˆž) reaching more than 1.00 (CLR > 1.00). In implementing sustainable management of spiny lobster for fishery resources, improvisation is needed in place of catching technologies. One of the recommendation is to add more fishing vessel (Lboat > 17.0 m) equipped with engines that are able to reach potential fishing ground in the west waters of Cemplung beach, Labangka.